The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1177/0883073816673263
|View full text |Cite
|
Sign up to set email alerts
|

Alexander Disease

Abstract: Alexander disease is a leukodystrophy caused by dominant missense mutations in the gene encoding the glial fibrillary acidic protein. Individuals with this disorder often present with a typical neuroradiologic pattern including white matter abnormalities with brainstem involvement, selective contrast enhancement, and structural changes to the basal ganglia/thalamus. In rare cases, focal lesions have been seen and cause concern for primary malignancies. Here the authors present an infant initially diagnosed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…AxD has presented in rare patients as a mass lesion, involving, for example, the brainstem or optic chiasm , suggesting the diagnosis of an astrocytoma. The Ki67 indices are low but raise above the lower levels present in the normal CNS.…”
Section: The Degree Of White Matter Pathology Varies and Predominatesmentioning
confidence: 99%
“…AxD has presented in rare patients as a mass lesion, involving, for example, the brainstem or optic chiasm , suggesting the diagnosis of an astrocytoma. The Ki67 indices are low but raise above the lower levels present in the normal CNS.…”
Section: The Degree Of White Matter Pathology Varies and Predominatesmentioning
confidence: 99%
“…При юношеской форме демиелинизация по данным МРТ выявляется преимущественно в лобных областях, при взрослых формах -в области мозжечка и ствола головного мозга [7].…”
Section: к л и н и ч е с к и е н а б л ю д е н и яunclassified
“…Alexander disease (AxD) is a rare but devastating disease that affects neural development and causes ataxia, seizures, intellectual dysfunction, and many other disabilities 1,2 . It is caused by heterozygous pathogenic variants of the Glial Fibrillary Acidic Protein (GFAP), 3–5 which codes for a major intermediate filament protein expressed exclusively in astrocytes within the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, ex vivo diffusion magnetic resonance imaging (MRI) has advantages over in vivo diffusion MRI in terms of a high signal‐to‐noise ratio and spatial resolution 34 . Although some neuroimaging studies have reported MRI features, particularly leukodystrophic features, of AxD, 2 to the best of our knowledge, no study has assessed brain pathways in AxD. Therefore, little is known about brain connectivity in AxD.…”
Section: Introductionmentioning
confidence: 99%